The efficiency of pig farming inputs in Minahasa Regency of North Sulawesi - Santa, N. M.; Manese, M. A. V.; Waleleng, P. O. V. (Diponegoro University, 2021)
The purpose of this study was to analyze the factors influencing the production and the efficiency of pig farming input in Minahasa Regency of North Sulawesi Province. The location was determined using the multistage random sampling method, determining regency, districts, and village, which have the highest pig population in North Sulawesi Province, so that Minahasa Regency, and four selected Districts (Sonder, Kakas, Tombulu and Tombariri), then 2 villages/district were taken. The sample was determined using a simple random method by taking 25 farmers in each district so that the total sample was 100 pig farmers, then the data was taken in January-July 2019. Variables measured were the number of pig production, the number of sows, the number of piglets, the number of feed (corn, concentrate, rice bran) and the number of labor. Data were analyzed using the Cobb-Douglas production function model with multiple linear regression and marginal product values calculations. The results showed that the efficiency of pig farming inputs was larger than one, meaning it was inefficient. This condition is still possible to increase pig production by increasing the number of sows, the number of piglets, the number of feed (corn, bran, concentrate), and the number of labor.